Konsep Meningkatkan Taqwa dalam Implementasi Kehidupan Perspektif Hamka dalam Tafsir Al-Azhar - Vatku Rohman, Mucholit; Nirwana AN, Andri; Dahliana, Yeti (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
Abstract: The implementation of piety is a form of faith to improve the characteristics of people who are devout in life. According to the Qur'an, taqwa is a person's personality towards Allah and this piety makes him submit and obey religious teachings by carrying out all commands and avoiding all prohibitions of Allah SWT. The aim of this research is to find out how to achieve devotion based on the perspective of Hamka's interpretation of Al-Azhar. The research uses qualitative methods with the type of library research with the Al-Azhar book as the main source, reinforced with secondary sources such as books, scientific works and related journals. The results of this research conclude that according to Buya Hamka, taqwa is not only limited to protecting oneself from the punishment of Allah SWT, but has a broader meaning, namely the spirit of worship, increasing pious deeds to be closer to Allah and spreading love and caring for fellow humans. In its implementation, piety is divided into 2 aspects, namely habluminallah and hablumminnas, namely maintaining a relationship with Allah, a devout servant must always carry out His commands and avoid His prohibitions and in maintaining relationships with other humans, a devout servant will spread a sense of compassion and affection. caring for others.